PSYCHOLOGICAL FACTORS OF FORMING TOLERANCE IN FAMILY RELATIONSHIPS (Universal International Scientific Journal, 2026)
This article analyzes the psychological factors that influence the formation of tolerance in family relationships. The role of personal characteristics, emotional intelligence, communicative culture and family values ​​in creating a tolerant environment, as well as mutual respect, empathy, patience and constructive conflict management processes between family members are considered as the main indicators of tolerance. Based on psychological processes in Uzbek families, psychological methods for strengthening tolerant behavior are highlighted.
Keywords: family relationships, tolerance, empathy, emotional intelligence, communication, conflict.